2016
DOI: 10.1177/1049909116636614
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Health-Care Providers Toward Advance Care Planning in Patients With Advanced Cancer and Congestive Heart Failure

Abstract: Attitudes toward ACP implementation vary considerably by medical specialty and medical condition, with oncologists in this study tending to feel more personal responsibility for these discussions with patients having cancer than cardiologists with their patients having heart failure. Robust implementation of ACP across the spectrum of medical diagnoses is likely to require a true collaboration between office-based PCPs and specialists in both the inpatient and the ambulatory settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 12 publications
3
37
0
Order By: Relevance
“…Negative social influences were addressed by preparing patients through brochures or public awareness campaigns (Glaudemans, de Jong, Onwuteaka Philipsen, Wind, & Willems, 2019;Howard et al, 2018;Wissow et al, 2004) and using patient video decision aids (Volandes et al, 2016). Positive social influences were created by promoting collaboration between primary care providers and specialists (Chandar et al, 2017) and using practice champions (Wissow et al, 2004). Motivation was increased by offering incentives-primarily in fee-for-service environments-to promote conversation (Fulmer et al, 2018) or performance feedback (Wissow et al, 2004).…”
Section: Adaptationsmentioning
confidence: 99%
“…Negative social influences were addressed by preparing patients through brochures or public awareness campaigns (Glaudemans, de Jong, Onwuteaka Philipsen, Wind, & Willems, 2019;Howard et al, 2018;Wissow et al, 2004) and using patient video decision aids (Volandes et al, 2016). Positive social influences were created by promoting collaboration between primary care providers and specialists (Chandar et al, 2017) and using practice champions (Wissow et al, 2004). Motivation was increased by offering incentives-primarily in fee-for-service environments-to promote conversation (Fulmer et al, 2018) or performance feedback (Wissow et al, 2004).…”
Section: Adaptationsmentioning
confidence: 99%
“…The guide allowed clinicians to obtain important information more efficiently, which has implications in a busy clinical practice. 15,62 The qualitative learnings also revealed enhanced confidence and comfort in initiating conversations and an intention to try the guide in practice. Although we were able to observe significant self-reported improvements, we express caution with these findings, given that these are subjective measures and numerous systematic reviews have concluded that training alone is insufficient to drive lasting improvements in practice.…”
Section: Discussionmentioning
confidence: 93%
“…4,13,14 Many barriers to communication have been identified: lack of knowledge about how to approach end-of-life communication, variation in attitudes about the right time to start, time constraints, and worries about patient reluctance. 13,[15][16][17][18][19] While multiple communication training programs have improved clinicians' skills, [20][21][22][23] several important challenges remain. First, some courses require two to four days of clinicians' time in workshops outside of their clinical setting.…”
mentioning
confidence: 99%
“…Further, because of inadequate time to discuss ACP in community settings, physicians and nurses may not be able to fully understand the wishes of older adults. It is for this reason that other healthcare workers are expected to discuss ACP more actively 25 , 26 ) .…”
Section: Discussionmentioning
confidence: 99%